Reforming the Limits of Discretion and Strengthening the Police Code of Ethics in Achieving Justice in Law Enforcement - Donny Widianto; Azis Budianto (Jurnal Impresi Indonesia, 2024)
Effective law enforcement requires clear regulations and high accountability. However, the use of discretion by law enforcement officers often poses a dilemma in maintaining a balance between flexibility and legal certainty. This study aims to analyze the legal regulations governing police discretion and code of ethics in Indonesia and to formulate a reform model to improve justice in law enforcement. This study uses a normative legal method with a legislative and conceptual approach, which examines written legal regulations and the underlying legal concepts. Data were collected from various relevant legal and scientific literature sources. The results of the study indicate that the use of undirected discretion can create injustice and reduce public trust in law enforcement officers. Reforms are needed to limit discretion by strengthening the police code of ethics and implementing clearer legal guidelines. The implications of this study include the development of policies that are more transparent, accountable, and in accordance with the principles of social justice. This reform is expected to increase the professionalism and legitimacy of the police in the eyes of the public.